Population Status of Tapanuli Orangutan (Pongo tapanuliensis) within the Renewable Energy Development and its Management Implications - Prasetyo, Didik; Hadiprakarsa, Yokyok; Kuswanda, Wanda; Sugardjito, Jito (Forestry Faculty, Universitas Hasanuddin, 2021)
To protect Tapanuli orangutan it is essential to understand the actual situation. It has been studied 15% of its population live outside the protected area facing a density disruption due to forest conversion. Several best management practices have been created and tested for different natural concession types. Yet, the main objective to reduce the impact and increase wildlife survival is far away from the goal. To improve our understanding of the species survival within ongoing project construction, we conducted population density monitoring prior- to post-construction time frames within the hydroelectric dam project. Also, we carried out spatial analysis to understand the land cover change and orangutan’s suitable habitat distribution. This study found that during high construction activities, orangutans were avoiding the threat sources, and returned when the disturbances reduced. These findings indicated orangutans are ecology flexible and have the capability to increase its survival, although the company’s involvement is crucial to facilitate the successes. Our study is based on indirect observation, and spatial modeling, which may lead to an uncertain conclusion. Further research on orangutan ecology and behavior is prioritized.